The Mkk2 MAPKK Regulates Cell Wall Biogenesis in Cooperation with the Cek1-Pathway in Candida albicans. - Elvira Román; Rebeca Alonso-Monge; Alberto Miranda; Jesús Pla (PLoS ONE, 2015)
The cell wall integrity pathway (CWI) plays an important role in the biogenesis of the cell wall in Candida albicans and other fungi. In the present work, the C. albicans MKK2 gene that encodes the putative MAPKK of this pathway was deleted in different backgrounds and the phenotypes of the resultant mutants were characterised. We show here that Mkk2 mediates the phosphorylation of the Mkc1 MAPK in response to cell wall assembly interfering agents such as zymolyase or tunicamycin and also to oxidative stress. Remarkably, mkk2 and mkc1 mutants display related but distinguishable- cell wall associated phenotypes and differ in the pattern of MAPK phosphorylation under different stress conditions. mkk2 and mkc1 mutants display an altered expression of GSC1, CEK1 and CRH11 genes at different temperatures. Combined deletion of MKK2 with HST7 supports a cooperative role for the Cek1-mediated and CWI pathways in regulating cell wall architecture under vegetative growth. However, and in contrast to Mkc1, Mkk2 does not seem to play a role in the virulence of C. albicans in the mouse systemic model or the Galleria mellonella model of infection.